2002
DOI: 10.1016/s0550-3213(01)00592-2
|View full text |Cite
|
Sign up to set email alerts
|

Lattice chiral symmetry and the Wess–Zumino model

Abstract: A lattice regularization of the supersymmetric Wess-Zumino model is studied by using Ginsparg-Wilson operators. We recognize a certain conflict between the lattice chiral symmetry and the Majorana condition for Yukawa couplings, or in Weyl representation a conflict between the lattice chiral symmetry and Yukawa couplings. This conflict is also related, though not directly, to the fact that the kinetic (Kähler) term and the superpotential term are clearly distinguished in the continuum Wess-Zumino model, wherea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 59 publications
7
52
0
Order By: Relevance
“…In fact this formulation agrees with a past suggestion [4,30] of the Wess-Zumino action in terms of the GinspargWilson operators.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…In fact this formulation agrees with a past suggestion [4,30] of the Wess-Zumino action in terms of the GinspargWilson operators.…”
Section: Introductionsupporting
confidence: 91%
“…It was first shown that the variables q L andq L cannot describe the topological properties, and the full physical contents are only described by the local Ginsparg-Wilson variables ψ L andψ L . The domain wall variables q andq in the infinite flavor limit, which themselves exhibit nice CP and charge conjugation properties, cannot help to resolve the difficulty associated with CP symmetry in chiral gauge theory [1] and the failure of the Majorana condition in the presence of chiral symmetric Yukawa couplings [4]. The conflict among the good chiral property, strict locality and CP (or charge conjugation) symmetry thus persists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations